PEMANFAATAN MEDIA SOSIAL INSTAGRAM SEBAGAI KOMUNIKASI PEMASARAN MODERN PADA BATIK BURNEH - Puguh Kurniawan (Kompetensi (Competence : Journal of Management Studies), 2017)
This study aims to utilize social media instagram as one of the forms of modern marketing communication. By utilizing social media instagram as one of the modern marketing communication aims to facilitate consumers in making purchases or transactions of an item and also seek information about goods to be purchased easily.The development of communication technology makes it easier for the flow of information exchange. The large number of instagram users make this social network increasingly functioning as a medium for doing business. Researchers want to know how big the role of instagram as an online business media on Batik burneh when used as an online business communication media. The results show that Instagram not only serves as a media campaign in online business, but also serves as a medium to communicate with potential customers. In addition instagram also provides a broad market share for online business players. This certainly gives its own impact on the sales of batik burneh. The conclusion resulting from this research is, instagram is a social network whose presence is increasingly maximized as a medium of doing business online. The role of which is instagram as a media campaign that is considered effective by the owner of Batik burneh, both instagram role as a medium of communication between Batik burneh with its customers. The three instagram acts as a container to find customers and the last instagram gives an impact to the increase of sales on Batik burneh